PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN UTANG, KEPUTUSAN INVESTASI DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Adhitya Rahman; Restu Agusti; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine and analyze the influence of dividen policy,debt policy, investment decisions and profitability to corporate value. Based on the criteria established in the purposive sampling method. This study used multiple regression analysis was used to test whether the independent variables affect the dependent variable. Based on test results, the variable debt policy, investment decisions and profitability had an influence on the acceptance of Corporate Value. While the variable dividen policy does not affect Corporate Value. The percentage effect of the independent variable on the dependent variable is 77,6%.Keywords: Dividen Policy,Debt Policy, Investment Decisions and Profitability CorporateValue